Operational Profiles for Statistical Testing of Distribution Management System - Basicevic, Ilija; Kupresanin, Ilija; Popovic, Miroslav (INFOCOMP Journal of Computer Science, 2011)
Each generation of software systems is becoming more complex. Also, software is becoming more important because today critical infrastructure systems depend on software. This paper presents the method applied in testing of a complex software system. For complex systems, it is very important to measure their reliability. Statistical testing based on operational profiles is a de facto industrial standard for this purpose. As a case study, we used Windows-based distribution management system that is used in electric power distribution utilities. A library that contains the analytical functions subsystem was tested. The paper gives an overview of the system and module being tested, and of the statistical method we applied. The main contribution of this paper is development of operational profiles for a realworld complex system. Two of the operational profiles we have developed for testing of the system are presented in detail. Another contribution is a new approach which supports generation of test cases onthe-fly: during execution of implementation under test on a test bed. This is possible by joining together the test case generator and the test bed.